Complexo de inclusão entre óleo de copaíba (Copaifera multijuga Hayne ) e HPQCD: desenvolvimento e caracterização para fins anti Trypanosoma cruzi - Taio, Fabrice (2024)
Chagas Disease, caused by the parasite Trypanosoma cruzi and primarily transmitted by the insect known as the 'kissing bug', represents a significant public health challenge in Latin America, affecting millions of people. In addition to medical implications, the disease is inherently linked to socio-economic and environmental factors such as disordered migrations, rapid urbanization, and environmental degradation. Given this challenging context, the search for new therapeutic strategies is crucial. In this context, this research aimed to develop and characterize inclusion complexes to improve the solubility of copaiba oil and evaluate its potential anti-Trypanosoma cruzi effect. For this purpose, copaiba oil and hydroxypropyl-G-cyclodextrin (OLC/HPGCD) were prepared by physical mixing (MF) and kneading methods (MLG). The complexes were then characterized using appropriate physicochemical methods. The results of the differential scanning calorimetry (DSC) showed endothermic peaks related to water loss, with HPGCD showing a peak at 70°C and OLC at 110°C, attributed to water molecule evaporation and volatilization, respectively. X-ray diffraction (XRD) analysis revealed crystallinity patterns characteristic of semicrystalline samples. Structural analyses by Fourier-transform infrared spectroscopy (FTIR) indicated the interaction between host and guest (OLC and HPGCD), demonstrating the potential of the developed inclusion complexes. The samples of HPGCD, MF, and MLG were analyzed with a scanning electron microscope (SEM) at various magnifications, revealing distinct morphological changes. HPGCD exhibited spherical particles, MF presented both spherical and fragmented particles, and MLG displayed irregular and porous shapes, indicating complete restructuring after processing.The anti-T. cruzi activities of HPGCD/OLC-MF and HPGCD/OLC-MLG complexes were comparable to Benznidazole at higher concentrations, although they were not effective at lower concentrations.